Alcohol related conditions represent a major psychiatric problem in emergency departments. Issue 6 (19th May 2006) - te Wildt, B T; Andreis, C; Auffahrt, I; Tettenborn, C; Kropp, S; Ohlmeier, M
Abstract : Background: Alcoholism represents a huge socioeconomic burden in most developed societies. Methods: In order to determine the impact of conditions associated with alcohol abuse on emergency care, in 2002 all patients with alcohol related pathology presenting to the emergency department (ED) of a large urban university hospital in Germany were assessed. Results: Of 2194 patients seen by psychiatrists in the ED, the 613 cases associated with alcohol abuse represented the largest diagnostic group (30.7%). Within this group, alcohol intoxication was the most frequent diagnosis (71.4%). Patients with an alcohol related condition needed treatment by different medical specialities and required diagnostic procedures significantly more often and consequently stayed significantly longer in the ED than patients with other psychiatric presentations. Conclusions: The generally underestimated problem of alcohol abuse in Germany demands an excessive amount of manpower and resources in EDs, where a high yet expensive standard of care is provided. Against this background, how far this burden can be reduced, both in EDs and in society in general, is discussed.